Kode Semiotika Roland Barthes pada Antologi Puisi Duka-Mu Abadi Karya Sapardi Djoko Damono - Abror, Muchlas; Subahtiar, Desta (Aksara: Jurnal Bahasa dan Sastra, 2024)
This research is motivated by the use of semiotic codes in poetry that presents ambiguous meanings that are difficult to interpret as a whole. To solve the problem, this research uses semiotic code reading according to Roland Barthes. The material object of this research is a poem entitled Prologue and Saat Sebelum Berangkat contained in the anthology Duka-Mu Abadi by Sapardi Djoko Damono. Methods and techniques of data collection by reading, listening, and recording. While heuristic, hermeneutic, and retroactive methods are used to analyze the data. The results of the analysis show that there are five semiotic codes consisting of prerioactive, hermeneutic, cultural, semantic, and symbolic. The prerioactive code in the Prologue poem is in the form of contemplation and meaning of life, and the realization that a loved one has passed away who then has to carry out a funeral for the corpse in the poem Saat Sebelum Berangkat (SSB). The cultural code of the Prologue poem shows the existence of Christian and Jewish religious culture, as well as the upper middle class in the SSB poem. The symbolic code in the Prologue poem is the use of the pronoun ‘Mu’ which refers to God, the Qain field, and the Gologota hill, while in the SBB poem it is a bouquet of flowers, the full world. The hermeneutic and semantic codes of both poems show the grief and loneliness of being left behind by a loved one. Keywords: Duka-Mu Abadi, Code, Roland Barthes, Semiotics